A joint STFT-HOC detection method for FH data link signals. (June 2021) - Zhou, Fan; Fan, Fangfang; Chen, Zihang; Zhang, Weikun; Wu, Sheng; Wang, Shaoqiang
Highlights: The high-order cumulant method is used to realize the effective recognition of 16QAM, MSK and 2PSK modulation signals. When the SNR is greater than −4 dB, the corresponding modulation recognition rate is 100%. The short-time Fourier transform is used to detect the constant frequency and non-constant frequency signals effectively. Abstract: The anti-interference, anti-interception, anti-spoofing ability and complex electromagnetic environment of the data link signal of the frequency hopping system pose formidable challenges to the reconnaissance of the frequency hopping signal. Therefore, this paper proposes a joint STFT-HOC detection method for FH data link signals. This method combines time-frequency analysis and high-order cumulant to realize effective detection of frequency hopping data link signals. Theoretical analysis and simulation experiments show that the proposed method can successfully detect the data link signal of the frequency hopping system when the signal-to-noise ratio is greater than −2 dB.